2015
DOI: 10.1038/npp.2015.166
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Interactions Between Stress and the Endocannabinoid System

Abstract: Stress affects a constellation of physiological systems in the body and evokes a rapid shift in many neurobehavioral processes. A growing body of work indicates that the endocannabinoid (eCB) system is an integral regulator of the stress response. In the current review, we discuss the evidence to date that demonstrates stress-induced regulation of eCB signaling and the consequential role changes in eCB signaling have with respect to many of the effects of stress. Across a wide array of stress paradigms, studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
522
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(554 citation statements)
references
References 277 publications
(437 reference statements)
24
522
0
8
Order By: Relevance
“…Thus, glucocorticoids enhance the production of endocannabinoids to counteract the activity of the HPA axis in many brain regions, including the hippocampus, the prefrontal cortex, and the hypothalamus (16,24). Overall, endocannabinoid production is induced by acute stress and acts by buffering stress-induced behavioral and endocrine stress effects (16,17,23).In this study we reveal a mechanism mediating stress-induced impairment of object-recognition memory consolidation. Using a combination of acute systemic and local pharmacological approaches and newly generated mouse lines, we found that peripheral and hippocampal CB1 receptors in dopamine β-hydroxylase (DBH)-expressing cells (i.e., adrenergic/noradrenergic cells) are both necessary and sufficient to impair object-recognition memory consolidation produced by acute stress.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, glucocorticoids enhance the production of endocannabinoids to counteract the activity of the HPA axis in many brain regions, including the hippocampus, the prefrontal cortex, and the hypothalamus (16,24). Overall, endocannabinoid production is induced by acute stress and acts by buffering stress-induced behavioral and endocrine stress effects (16,17,23).In this study we reveal a mechanism mediating stress-induced impairment of object-recognition memory consolidation. Using a combination of acute systemic and local pharmacological approaches and newly generated mouse lines, we found that peripheral and hippocampal CB1 receptors in dopamine β-hydroxylase (DBH)-expressing cells (i.e., adrenergic/noradrenergic cells) are both necessary and sufficient to impair object-recognition memory consolidation produced by acute stress.…”
mentioning
confidence: 75%
“…The endocannabinoid system is an endogenous neuromodulatory system playing a relevant role in the regulation of the stress response (13)(14)(15)(16)(17)(18). Endocannabinoids, such as 2-arachidonoylglycerol (2-AG) and N-arachidonoyl ethanolamine (anandamide; AEA), act mainly at two types of cannabinoid receptors, cannabinoid type-1 (CB1) and type-2 (CB2) receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the CB1 receptors have analgesic effects at the peripheral sensory afferents, in the dorsal horn of the spinal cord, the periaqueductal grey (PAG) and the brainstem (Woodhams et al 2015). In addition, endocannabinoids are indispensable in the development of acute stress induced analgesia (Morena et al 2016), and the downregulation of endocannabinoid signalling is an important mechanism in the development of chronic stress induced hyperalgesia (Jennings et al 2015; Lomazzo et al 2015; Rea et al 2014). However, more and more evidence suggests that endocannabinoids mainly influence the affective component of pain, in which amygdala activity has a pivotal role, compared to the sensory aspects (Lee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…How fear is modulated by stress is beginning to be understood at a variety of levels, including both neural circuitry and underlying molecular mechanisms. A particularly interesting set of findings over the past few years has revealed how the endogenous cannabinoid system is involved in both extinction of fear and in modulating the stress response, as reviewed in detail at the end of this section (Morena et al, 2016).…”
mentioning
confidence: 99%